跨国主义与新加坡琼人= Transnationalism and Hainanese in Singapore - 周文培 Zhou, Wenpei (Nanyang Technological University, 2021)
本文以新加坡琼人为研究对象，运用“跨国主义”理论视角，对比分析不同发展阶段琼人的跨国行为特征，以及跨国实践活动所联结的多重社会关系网络。从琼人迁移的背景、原动力、渠道，论证当初一批批琼人离开故土到新加坡闯荡，目的不是为了“分离”，而是更好的“联系”。唯有如此，才能更好地联系家人、家庭和家乡，改变其家庭生活状况和家乡经济发展。文中又通过变量之轴兼及不同时期，探索新加坡琼人为适应不同的生存环境，调适发展形成不同的生态特征和适应过程，呈现出新加坡琼人的双重文化生活和双重民族主义特点。琼人在新加坡建立起属于自己的“小生境—通道”，使之成为纽带的空间维度，构成特定的移民生态跨国模式，并通过社团组织的凝聚力和影响力，成为在新加坡困难和矛盾的帮扶者，权益和诉求的维护者。本文从琼人的生根、发芽到茁壮演进史源，解读琼人跨国身份认同嬗变的原因，剖析琼人跨国网络建构的内在脉络。这些都对丰富海外华人研究的内涵具有重要的学术意义，也对开展人类学生存和发展的思考具有重要现实意义。This dissertation studies the Hainanese in Singapore from the mid-nineteenth century to the present. It employs a mobile perspective to analyse the transnational activities of Hainanese emigrants at different stages of Singapore history, and the multiple social networks that spanned Singapore and Hainan that they created. By tracing the background, motivations, and migration channel of the Hainanese, this study reveals that for these emigrants, leaving home was not about “separation” but finding new and better ways for “connection.” Only by doing so,could they better the living standard of their family members, and improve the economic conditions of their hometowns. In Singapore, the Hainanese adapted their survival strategies flexibly in response to the changing historical conditions of the island, and in the process demonstrated their comfort in living under the very different cultural and political conditions of Singapore and Hainan. They did it by creating a special “niche” in Singapore -- through their native-place bond, the Hainanese formed a tightly knitted emigrant community whereby they not only helped one another in times of need, but also banded together to fight for community rights and benefits. This study on the Hainanese emigrants’ roots in the homeland, their adaptability in the place of settlement, their evolving identity, and their construction and maintenance of transnational networks have important implications for our understanding of overseas Chinese studies in general, and the survival of Chinese emigrants.